Patient experiences in primary health care services in the JKN era: A qualitative study - Hartono, Hartono; Siagian, Masryna; Siahaan, Marlina Elpiani; Tambunan, Ester Theresia; Sibagariang, Eva Ellya (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Implementing JKN (Jaminan Kesehatan Nasional) in primary healthcare is expected to support the accessibility and success of early treatment and reduce the burden on secondary healthcare facilities. Patient experience can provide information on the quality of health services from different perspectives to provide valuable input for improving the quality of care. This study explores patients' experiences in utilizing health services in primary healthcare services in the JKN era. This research used a qualitative approach with a case study design conducted at the Puskesmas Tangkahan Durian, Langkat Regency. The researchers collected data through oral questioning with 11 informants, following previously developed in-depth interview guidelines. Researchers have also made direct observations of the health services carried out. The study results showed that patients had a fairly positive experience accessing health services at public health center/puskesmas. There was no discrimination or difference in treatment among health workers in JKN patients or general patients. Patient complaints are only in the location of the seats in the waiting room that are not arranged to interfere with patient mobility. Another criticism is that officers do not come to the public health center on time according to predetermined operating hours. Public health center management should increase the discipline of officers regarding service operating hours and consider the seating layout in the patient waiting room.